Asertivitas ibu hamil terhadap perilaku merokok suami (Berita Kedokteran Masyarakat (BKM), 2018)
The assertive intention of pregnant women toward husbands’ smokingPurpose: This study aimed to identify the aspect that influencing the intentions of the assertive behavior of pregnant women related to husbands’ smoking behavior at home.Methods: This study was the part of the thesis as well as part of the Peer Health Secondhand Smoke-Low Birth Weight intervention study in North Lombok District, West Nusa Tenggara Province. Design study in this research used a cross-sectional approach. Secondary data used in this study, which was from baseline data of Peer Health SHS-LBW intervention. The population of this study was pregnant women with gestational age ≤ four months. Sample selection technique used criterion sampling. The number of research samples as many as 1291 respondents. Results: There was a relationship between knowledge (p-value = 0.036; OR= 1.286; CI 95%= 1.017-1.627), attitude (p-value= 0.000; OR = 3.120; CI 95%= 2.444-3.982) and information exposure (p-value= 0.000; OR= 2.497; CI 95%= 1.582-3.942) with the intention of assertive behavior of pregnant women related to husbands’ smoking behavior at home. The existence of the relationship was because the respondents were exposed by the information of the harmful effects of cigarettes, have good knowledge, non-smoker families who support them to behave assertively.Conclusions: Interventions such as increased knowledge and attitudes, as well as the strengthening of smoking ban rules to improve the assertive behavior intention of pregnant women toward husbands smoking behavior at home